Assessing urbanization quality using structure and function analyses: A case study of the urban agglomeration around Hangzhou Bay (UAHB), China. (October 2015) - Zhou, De; Xu, Jianchun; Wang, Li; Lin, Zhulu
Abstract: Urbanization quality assessment is a test of land space, industrial economy, institutional politics, social and cultural reconstruction, and eco-environmental sustainability. We propose a specific path to improving urbanization quality in the urban agglomeration around Hangzhou Bay (UAHB), a region in eastern China's Zhejiang Province. The objective of our study was to develop an urbanization quality assessment methodology by analyzing relationships between the structure and the function of a system and establishing a comprehensive index system based on systems science. We demonstrated through a case study of composite urbanization quality for the UAHB, which is undergoing rapid urbanization. The comprehensive indexes for assessing urbanization quality were conducted using thirty-two indicators and the entropy weight method (EWM). Results from this study showed that the urbanization quality was strongly influenced by system structure and function and their relationships. The driving force analysis for urbanization quality evolution also showed that the overall pattern of the relative importance of the system structures for all cities in the UAHB displayed strong variability at the spatial scale and both system structure and system function have changed in the past 10 years at the temporal scale. To maintain a sustainable urbanization process, we proposed a set of optimization methods for the new-type urbanization development in China based on our study of UAHB. Highlights: Urbanization development is a complex process affected by various factors. An urbanization quality assessment was conducted in a region in China's eastern coast. A system's structure and function analyses can be used to assess urbanization quality. A system's structure has a significant influence on its function.